Identification of SLC20A1 and SLC15A4 among other genes as potential risk factors for combined pituitary hormone deficiency - Simm, Franziska; Griesbeck, Anne; Choukair, Daniela; Weiß, Birgit; Paramasivam, Nagarajan; Klammt, Jürgen; Schlesner, Matthias; Wiemann, Stefan; Martinez, Cristina; Hoffmann, Georg F.; Pfäffle, Roland Werner; Bettendorf, Markus; et al. (Genetics in medicine, 2018)
Combined pituitary hormone deficiency (CPHD) is characterized by a malformed or underdeveloped pituitary gland resulting in an impaired pituitary hormone secretion. Several transcription factors have been described in its etiology, but defects in known genes account for only a small proportion of cases. To identify novel genetic causes for congenital hypopituitarism, we performed exome-sequencing studies on 10 patients with CPHD and their unaffected parents. Two candidate genes were sequenced in further 200 patients. Genotype data of known hypopituitary genes are reviewed. We discovered 51 likely damaging variants in 38 genes; 12 of the 51 variants represent de novo events (24%); 11 of the 38 genes (29%) were present in the E12.5/E14.5 pituitary transcriptome. Targeted sequencing of two candidate genes, SLC20A1 and SLC15A4, of the solute carrier membrane transport protein family in 200 additional patients demonstrated two further variants predicted as damaging. We also found combinations of de novo (SLC20A1/SLC15A4) and transmitted variants (GLI2/LHX3) in the same individuals, leading to the full-blown CPHD phenotype. These data expand the pituitary target genes repertoire for diagnostics and further functional studies. Exome sequencing has identified a combination of rare variants in different genes that might explain incomplete penetrance in CPHD.
Advance online publication: 26 October 2017
Gesehen am 19.08.2019